Quality Management Strategy in Improving Educational Institution Accreditation Results - Muhammad Alfi Alfaridli; Dian Zulfatul Iman; Ummi Hani’ (Teewan Journal Solutions, 2025)
This study focuses on quality management strategies in improving the accreditation results of educational institutions, by examining in depth how managerial practices are implemented systematically and sustainably. The approach used is qualitative with a case study type, which allows for in-depth exploration of the process, dynamics, and context of implementing quality strategies at Madrasah Aliyah Nurul Jadid which has obtained